Determinação da estabilidade de fases à 1300oC do sistema Al2O3-Y2O3-Ta2O5 - Oliveira, Juliana Pereira De (2023)
Ceramics of pseudo-ternary Al2O3-Y2O3-Ta2O5 system have potential for applications in engineering areas due to the mechanical properties in compression and fracture toughness of Al2O3-Y2O3 ceramics and others Al2O3-Ta2O5 ceramics related to catalytic processes. However, no information on the phase stability of the Al2O3-Y2O3-Ta2O5 system was found in the literature. Thus, the present research aims to determine the phase stability at 1300ºC of this pseudo-ternary system. Information from the corresponding pseudo-binary systems will be used for an initial proposition of possible biphasic and/or three-phase regions. Based on this information, different chemical compositions, in mol-%, were considered. After weighing, the mixtures of Al2O3, Y2O3 and Ta2O5 powders were homogenized in a ball mill for 10 min, using a WC vial (80mL) and alumina balls (10mm in diameter), to minimize their contamination. In sequence, the cylinder samples with 10 mm diameter were prepared by axial pressing of 187 MPa. The green compacts of Al2O3-Y2O3-Ta2O5 ceramics were heat-treated at 1300ºC for 72 h and 222 h, aiming to obtain equilibrium microstructures. Samples of heat-treated Al2O3-Y2O3-Ta2O5 ceramics were characterized by means of X-ray diffractometry, scanning electron microscopy and energy dispersive spectrometry techniques. The results have confirmed the existence of three-phase Y2O3+Y4Al2O9+Y3TaO7 and YTa7O19+AlTaO4+Ta2O5 regions from the 11.11Al2O3 – 8.33Ta2O5-80.56Y2O3 and 16.67Al2O3-78.57Ta2O5-4.76Y2O3 (mol-%), respectively.